A Capstone Course in Ecuador: The Andes/Galápagos Volcanology Field Camp Program. Issue 3 (7th August 2017) - Kelley, Daniel F.; Uzunlar, Nuri; Lisenbee, Alvis; Beate, Bernardo; Turner, Hope E.
ABSTRACT: We developed and implemented the Galapagos Volcanology Field Camp, a 3 week, 3 credit hour course for upper-level university students with a major course of study in geology. The course is offered by the South Dakota School of Mines and Technology, is open to any student, and is usually populated by students from many universities across the U.S. The course offers the essential skills of field geology, such as lithologic description, unit identification and correlation, stratigraphic logging, and geologic mapping, taught exclusively in an environment of volcanic rocks. Beginning in the subduction setting of the Andes, students are introduced to the regional volcanic and tectonic history. The course visits volcanoes that have produced andesitic, dacitic, and rhyolitic products. Students study lava flows, pyroclastic flows, ignimbrites, lahar flows, and debris avalanche deposits. Students are also introduced to the volcanic hazards and monitoring efforts in Ecuador. During the second phase of the course, the group flies to the Galápagos Islands to examine the basaltic features of hotspot volcanism. Students study recent lavas erupted from well-developed shield volcanoes, lava tunnels and collapse features, and the history of uplift, subsidence, and sea-level variation. Through design and implementation of this program, a sequence of exercises has been found that build a robust curriculum while fitting into an itinerary that is logistically feasible. Study of volcanic deposits in this classic setting leads to strong student learning, with 84% of students who have participated scoring higher than 80% on activities designed to assess the stated learning objectives.